Perspective Of Security Intelligence in Law Enforcing Terrorism in Indonesia - Mulya, Ade; Ismail, Marzuki; Jumaeng, Suardi (International Journal of Social Service and Research, 2023)
Handling criminal acts of terrorism from a counterintelligence perspective to dissect activities carried out in the counterintelligence dimension of personnel security. The purpose of this article is to discuss the high threat and risk of terrorist attacks on personnel who handle terrorist crimes. The research method used prioritizes normative studies of literature on counterintelligence and counterterrorism with an emphasis on counterintelligence efforts for personnel security. In the end, the results of this research show that counterintelligence is very relevant to handling terrorism by working together and collaborating with various parties, but the counterintelligence perspective on personnel security has not become a strengthening and priority for regulators in efforts to suppress terrorism.